Efektivitas Media Interaktif Berbasis Digital dalam Meningkatkan Berpikir Kritis Siswa pada Pembelajaran Mahārah Qirā’ah di MTs Plus Al-Azhar Wlingi Blitar - Yuliani, Luluk; Ritonga, Apri Wardana; Machmudah, Umi (STAI Ali bin Abi Thalib Surabaya, 2025)
The advancement of digital technology has brought significant changes to the field of education, one of which is trough the integration of digital-based interactive media as a learning tool. This study aims to explore the effectiveness of using digital-based interactive educational media in enhancing students’ creative thinking skills in mahārah qirā’ah at MTs Plus Al-Azhar Wlingi Blitar. This research employed a quantitative method with a one-group pre-test and post-test design. The sample consisted of 22 seventh-grade students selected using a saturated sampling technique. The research instruments included tests measuring students’ critical thinking skills before and after the implementation of educational digital-based interactive media, as well as observations of the learning process. The analysis showed a significant improvement in students’ critical thinking, as evidenced by an average N-Gain score of 0.7687, categorized as high. The validity and reliability tests indicated that the test items were valid and highly reliable (Cronbach's Alpha = 0.807). The data also met the assumptions of normality and homogeneity, which reinforced the validity of the results. During the learning process, students demonstrated active engagement and improved performance across various levels of Bloom's taxonomy, from understanding to creating. Thus, digital-based interactive media have proven to be an effective and enjoyable medium for enhancing creative thinking and text comprehension in Arabic language learning. This study contributes to the development of innovative instructional strategies that align with the characteristics of the digital generation.